2004
DOI: 10.1097/01.sla.0000128686.51815.8b
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results With Resection of Radiation-Induced Soft Tissue Sarcomas

Abstract: The increasing utilization of adjuvant radiation therapy, especially for early-stage breast cancer mandates long-term follow-up to detect radiation-induced sarcoma. Surgical resection remains the primary therapy, but 5-year survival remains approximately 40%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
163
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(181 citation statements)
references
References 24 publications
11
163
2
5
Order By: Relevance
“…The length of time required between radiation exposure and sarcoma formation is the one criterion that has been modified by most investigators from the several year requirement originally proposed. This latency period is necessary to differentiate a RT-induced sarcoma from a second primary that may predate the radiation; because no accurate molecular or pathologic markers exist, any spontaneous sarcomas that may appear in a radiation field cannot reliably be excluded from analysis [15]. The minimum latency period used to call a tumor radiation-associated, in the literature, is 2 to 5 years and the median latency period is 10 to 14.3 years [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The length of time required between radiation exposure and sarcoma formation is the one criterion that has been modified by most investigators from the several year requirement originally proposed. This latency period is necessary to differentiate a RT-induced sarcoma from a second primary that may predate the radiation; because no accurate molecular or pathologic markers exist, any spontaneous sarcomas that may appear in a radiation field cannot reliably be excluded from analysis [15]. The minimum latency period used to call a tumor radiation-associated, in the literature, is 2 to 5 years and the median latency period is 10 to 14.3 years [10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous irradiation may have played a role in obscuring anatomic and tumor planes, preventing surgeons from appreciating true tumor margins. This underscores the necessity for aggressive and wide resections, especially considering that a positive surgical margin (gross or microscopic) will reduce survival by nearly half [22]. Radical resection of the adjacent structures has no advantage in the local control of the disease when compare to a three dimensional wide local excision [7,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radical surgery (R0 resection) is possible in 50% to 75% of patients who have RAS located in any part of the body and results in 5-year local relapse-free survival rates of 34% to 46% and 5-year survival rates of 27% to 44%. 7,17,31,32 A review of all 92 patients of angiosarcoma after breast-conserving therapy reported in the English literature revealed that 55 of 75 patients (73%) with at least 1 year of follow-up developed a local recurrence after mastectomy (n ¼ 72) or wide local excision (n ¼ 3). 33 In that review, all patients who received adjuvant radiotherapy (n ¼ 1) and/or chemotherapy (n ¼ 3) experienced a local recurrence.…”
Section: Discussionmentioning
confidence: 99%